Analysis and Simulation of Functional Stress Degradation on VDOMS Power Transistors - M. Zoaeter; B. Beydoun; M. Hajjar; M. Debs; J-P Charles (Active and Passive Electronic Components)
The use of VDMOS transistor under certain functional stress conditions produces a modification of its physical and electrical properties. This paper explores the physical analysis and SPICE simulation of the degradation effects related to the component micronic structure, and points out the degraded parameters following this stress.